Assessing the Relationship Between Depression and Obesity Using Structural Equation Modeling - Dragan, Alina (My University, 2005)
In this project we used structural equation modeling to analyze the data collected for the Canadian Community Health Survey (CCHS) Cycle 1.2 - Mental Health and Well-Being conducted by Statistics Canada. The data are cross-sectional.
We looked at the relation between depression and obesity adjusting for gender, socioeconomic status, gene-environment interactions, eating and physical activity and stress.
We used the AMOS and Mplus softwares to analyze our data. The first one used continuous variables for depression ("persistence of depression", in years) and obesity ("body mass index"-BMI), while the second used categorical variables: lifetime depression, 12 month depression and obesity (normal weight, overweight and obese). We also used two variables to measure different aspects of stress: self-perceived ability to handle an unexpected problem and work stress-social support.
We fitted the models across the entire data, but also across different groups: males versus females and groups based on gender and BMI.
The results indicated that the relationship between depression and obesity is different across gender.
The limitations of the study are also discussed.
Keywords: depression, obesity, structural equation, modeling, mental health, gender, socioeconomic